FISHING TECHNOLOGY IN NETWORK FISHING TOOLS INSANG (gillnet) IN PULAU JAMBU VILLAGE KECAMATAN KUOK KAMPAR DISTRICT, RIAU, PROVINCE - Nurhamidah Hasibuan; Alit Hindri Yani; Ronald M Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in April 2018 in Pulau Jambu Village, Kuok District, Kampar Regency, Riau Province. The purpose of this study was to determine the construction of gill net fishing equipment in general, to know the technique of gill net operation, to find out the results of gill net catches, to know the level of gillnet net fishing environment friendliness. The method used in this research is survey method. Data analysis using descriptive analysis. There are two ways to operate the gill net (gillnet), namely the decrease in the net (setting) and the lifting of the net (hauling). From the assessment of the level of friendliness of the gill net fishing gear (gillnet), a score of 29.7 was obtained, so the gill net fishing gear was classified as a very environmentally friendly fishing gear.                                                                                                        Keywords:fishing technology, operation, environmental friendliness